Synthesis and Antibacterial Assay of 9-Substituted Aryl-1,8-dioxo-octahydroxanthenes - Lakshmi Narasimha Murthy, Yellajyosula; Mahesh, Palla; Rama Devi, Bhoomireddy; Durgeswarai, L.K.; Mani, Palla (Asian Journal of Chemistry, 2014)
The present report highlights the heterogeneous catalytic activity of nano copper ferrite for the one pot synthesis of 9-substituted aryl-1,8-dioxo-octahydroxanthenes when dimedone reacts with various aromatic aldehydes under solvent free conditions, catalyzed by nano catalyst. The main advantageous of this protocol includes excellent yields, mild reaction conditions and short reaction times.